2011
DOI: 10.1111/j.1570-7458.2011.01162.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the fungal endophyte Neotyphodium occultans for resistance to the rice leaf bug, Trigonotylus caelestialium, in Italian ryegrass, Lolium multiflorum

Abstract: Fungal endophytes of the genus Neotyphodium (Ascomycota: Clavicipitaceae) form symbiotic associations with many grass species of the subfamily Pooideae, including some important forage and turf grasses from the genus Lolium. Some Neotyphodium-infected grasses have enhanced resistance to the rice leaf bug, Trigonotylus caelestialium (Kirkaldy) (Heteroptera: Miridae), one of the major pests in rice production in Japan. The insects can grow on Lolium grasses and thus cause a conflict of interest between productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Endophyte infection, which signiÞcantly decreased larval weight gain in young grasses, was correlated with decreased emigration. Increased emigration away from Eϩ plants has been detected with both chewing and sucking insects in turfgrasses (Richmond and Shetlar 1999, 2000, while avoidance of Eϩ plants is often associated with movement toward E-plants (Carriere et al 1998, Clement et al 2011, Shiba et al 2011. Other turf feeding insects are not affected by endophyte-mediated defenses (Williamson and Potter 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Endophyte infection, which signiÞcantly decreased larval weight gain in young grasses, was correlated with decreased emigration. Increased emigration away from Eϩ plants has been detected with both chewing and sucking insects in turfgrasses (Richmond and Shetlar 1999, 2000, while avoidance of Eϩ plants is often associated with movement toward E-plants (Carriere et al 1998, Clement et al 2011, Shiba et al 2011. Other turf feeding insects are not affected by endophyte-mediated defenses (Williamson and Potter 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Our study extends these previously reported facultative endophyte-mediated negative effects on aphids more broadly to other hemipterans to include L. hesperus plant bugs (Miridae) and N. viridula stink bugs (Pentatomidae). To our knowledge, the only other evidence to date of fungal endophyte-mediated effects on nonaphid hemipterans involves the obligate clavicipitaceous Neotyphodium-Lolium fungus-ryegrass system (Shiba & Sugawara, 2005;Shiba et al, 2011). For example, Shiba & Sugawara (2005) showed that the presence of N. lolli as an endophyte in perennial ryegrass, Lolium perenne, deterred feeding on inflorescences by both first instar and adult rice leaf bugs, Trigonotylus caelestialium Kirkaldy (Heteroptera: Miridae).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, these endophytes often confer tolerance to abiotic (Kannadan and Rudgers, 2008) and biotic (Elmi et al, 2000;Shiba et al, 2011) sources of stress. In the present study, the decrease in the number of M. incognita J2 moving towards E+ plants and in the number of J2 penetrating the roots of E+ plants suggests that presence of the endophyte N. coenophialum might partly contribute to the anti-nematode properties of endophyte-host associations.…”
Section: The Antagonism Of Neotyphodium-host Associations Towards M mentioning
confidence: 99%
“…increasing resistance to insect pest, being more competitive and thriving better with limited resources (Malinowski and Belesky, 2000;Shiba et al, 2011). It suggests that the endophytic fungi can play important ecological roles in plant communities (Clay and Holah, 1999).…”
Section: Introductionmentioning
confidence: 99%